Expression of CEA, CA-125 and SCC antigen by biological fluids associated with pregnancy - Sarandakou, A.; Kontoravdis, A.; Kontogeorgi, Z.; Rizos, D.; Phocas, I. (European Journal of Obstetrics and Gynecology and Reproductive Biology, 1992)
Carcinoembryonic antigen (CEA), cancer antigen 125 (CA-125) and squamous cell carcinoma (SCC) antigen were measured in 56 full-termed pregnancies by enzyme-immunoassays (EIA-MEIA). The measurements were done in maternal serum (MS), umbilical cord blood (UCB) and amniotic fluid (AF) samples, during delivery. Very high antigen levels were found in AF samples (median: CEA = 124 ng/ml; CA-125 = 710 U/ml; SCC = 710 ng/ml) compared to UCB and MS. CEA and SCC showed significantly lower value's in MS (0.6 and 1.7 ng/ml, respectively) than in UCB (1.6 ng/ml, P = 7.7 × 10-9; 3.55 ng/ml, P = 6.5 × 10-6, respectively), while CA-125 had significantly higher values in MS (6 U/ml) than in UCB (0.0 U/ml, P = 17 × 10-6; Wilcoxon paired test). All CEA values in MS were below cut-off (≤ 5 ng/ml), while 10% of CA-125 and 30% of SCC values were above cut-off (≤ 35 U /ml and ≤ 2.5 ng/ml, respectively). Amniotic fluid CEA with meconium had higher values (P = 0.0002), while the highest CA-125 values in AF samples were found in primiparae (P = 0.02). Moreover SCC in AF samples from vaginal delivered pregnancies showed significantly higher values, compared to those from cesarean section (P = 4.2 × 10-7; Mann-Whitney U-test). Thus, our findings suggest that pregnancy has an influence on maternal serum SCC and CA-125 values, while CEA is independent of gestation and seems to conserve its diagnostic value during pregnancy as well. © 1992.
Keywords: Cancer antigen 125; Carcinoembryonic antigen; Oncofetal antigen; Squamous cell carcinoma antigen